2021
DOI: 10.1039/d1cp00653c
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties and energy transfer processes in Tb3+-doped ZnSe quantum dots

Abstract: Tb3+-doped ZnSe quantum dots (QDs) with Tb content in the range of 0.5 - 7% were successfully synthesized by a wet chemical method. X-ray diffraction (XRD) and transmission electron microscopy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…36–40 The emission process of Er 3+ ions in hosts is due to different recombination mechanisms or energy transfer. The lifetimes of the samples were determined from the PL decay curve by fitting with a bi-exponential function, which is given as: 44,45 where, τ i is the lifetime, and A i is the pre-exponential factor. The average lifetime can be calculated using the following equation: 46,47 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…36–40 The emission process of Er 3+ ions in hosts is due to different recombination mechanisms or energy transfer. The lifetimes of the samples were determined from the PL decay curve by fitting with a bi-exponential function, which is given as: 44,45 where, τ i is the lifetime, and A i is the pre-exponential factor. The average lifetime can be calculated using the following equation: 46,47 …”
Section: Resultsmentioning
confidence: 99%
“…OH groups and rests of acetates), energy transfer between Er 3+ ions or from an Er 3+ ion to face states and killer centers which always exist in quantum dots, etc. 48 The nonradiative probability ( W NR ) and quantum efficiency ( η ) of the 4 I 13/2 level were calculated using the following formulas: 29,44 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their bandgap energies can be altered by changing the NC core/shell structure, composition modification, and doping. 15–18…”
Section: Introductionmentioning
confidence: 99%
“…Their bandgap energies can be altered by changing the NC core/shell structure, composition modication, and doping. [15][16][17][18] For doped semiconductor NCs, F. J. Willars-Rodríguez et al studied the effects of aluminum doping in CdS. 19 The authors found that the metal cations in the crystalline structure of CdS modied the electrical and structural properties of the undoped material.…”
Section: Introductionmentioning
confidence: 99%